Dermatitis dan Gambaran Histologi Kulit Anjing yang Ditangani di Rumah Sakit Hewan Pendidikan Universitas Udayana - Suwiti, Ni Ketut; Besung, I Nengah Kerta; Widyastuti, Sri Kayati (Jurnal Veteriner; Vol 23 No 4 (2022), 2022)
Research on the incidence of dermatitis in dogs and its histopatology has been carried out. This study was aims to identify the causes of dermatitis, and to determine the histopatology of the skin of dogs suffering from dermatitis, as well as its occurrence in female and male dogs, both domestic and breed dogs that are caged or not. The study was conducted for 10 months, at the Teaching Animal Hospital, Udayana University, with a total sample of 470 individuals. Identification of the cause of dermatitis was taken from skin scrapings added with 10% kalium hydroxide (KOH) observed with a 400 times magnification of light microscope. Meanwhile, for histopatology examination, a dog skin biopsy was taken and histology preparations were made, and staining with Haematoxilin-eosin methode. Observations were made with a light microscope with 100 and 400 times magnification. The results showed that the histopatology of the skin of dogs suffering from dermatitis was found: inflammatory cells infiltration, hyperkeratosis, necrosis, hyperplasia and hydropic degeneration, and segments of Sarcoptes scabiei. The germs that cause dermatitis were identified: Aspergillus sp., Microsporum canis, M. gypseum, and Trichophyton rubrum. Dermatitis was more often found in domestic dogs (56%), adult dogs (68%) and unkept dogs (63%), while gender had no effect on the incidence of dermatitis. Conlusion of this research that, there was a similar in the histopatology feature of dermatitis dogs, caused by fungi or parasites.